A Hydrazine‐Nitrate Flow Battery Catalyzed by a Bimetallic RuCo Precatalyst for Wastewater Purification along with Simultaneous Generation of Ammonia and Electricity. (31st March 2023) - Zhu, Weijie; Zhang, Xiaoyi; Yao, Fen; Huang, Runping; Chen, Yue; Chen, Chaolong; Fei, Jiawei; Chen, Yunqing; Wang, Zhoucheng; Liang, Hanfeng
Abstract: The traditional technologies for industrial and agricultural effluent treatment are often energy‐intensive. Herein, we suggest an electrochemical redox strategy for spontaneous and simultaneous decontamination of wastewater and generation of both fuels and electricity at low cost. Using hydrazine and nitrate effluents as a demonstration, we propose a hydrazine‐nitrate flow battery (HNFB) that can efficiently purify the wastewater and meanwhile generate both ammonia fuel and electricity with the assistance of our developed bimetallic RuCo precatalyst. Specifically, the battery delivers a peak power density of 12 mW cm −2 and continuously operates for 20 h with an ammonia yield rate of ca. 0.38 mmol h −1  cm −2 under 100 mA cm −2 . The generated electricity can further drive a hydrazine electrolyzer to produce hydrogen fuel. Our work provides an alternative pathway to purify wastewater and generate high value‐added fuels at low cost. Abstract : This work reports a new and general electrochemical redox strategy for spontaneous and simultaneous decontamination of wastewater and generation of both fuels and electricity at low cost. Using hydrazine and nitrate effluents as a demonstration, the bimetallic RuCo precatalyst can efficiently catalyze both the hydrazine oxidation and nitrate reduction reactions so as to assemble a hydrazine‐nitrate flow battery with electricity and ammonia generation.